Predatory Journals: How Should We Understand and Evaluate Them? (Journal of Contemporary Educational Policies and Practices, 2025)
Predatory journals have emerged as a growing challenge to academic integrity worldwide, driven by increasing publication pressures and ongoing changes in scholarly publishing. Although numerous lists, warning signs, and checklists have been proposed to identify such journals, the lack of consensus and standardized approaches has created confusion among researchers and institutions. This paper is presented as an opinion piece that reflects on existing debates and practical experiences related to predatory publishing. Drawing on the literature and the authors’ analytical perspectives, the paper discusses common misunderstandings surrounding predatory journals and highlights limitations of list-based evaluation approaches. It argues for a more cautious, context-sensitive, and process-oriented approach to assessing journals, emphasizing transparency, peer-review practices, editorial governance, and publisher credibility. By offering reflective insights rather than empirical findings, this article aims to stimulate critical discussion and support more informed decision-making in journal evaluation.